(untitled) (Palíndromo, 2024)
The article aims to map academic production about the term “artist-teacher” in art schools on the CAPES (Coordination for the Improvement of Higher Education Personnel of Brazil) journal portal. The “artist-teacher” is a professional who works both in the artistic, cultural production field and in the educational sphere. This term marks a hybridism characteristic of our current time, in which we cannot affirm that the subject’s identity is unique, individual, but rather, multiple (Santaella, 2007). The focus of the research is triggered by the selection of articles published in peer-reviewed scientific journals, a choice driven by the constant updating of this type of academic production. The state of the art made it possible to carry out an assessment of the research, demonstrating that the term has been increasingly used, especially in the last decade (2010-2020) in the Visual Arts and Art/education fields.